المؤثرات الكلامية في الفكر النحوي العربي نحاة القرن الرابع الهجري أنموذجا - ريمي, إدريس (جامعة الوادي - University of Eloued, 2021)
ملخص: هذا البحث دراسة تاريخية في النحو العربي، أُبرز من خلالها تأثير مناهج علماء الكلام وأساليبهم ومصطلحاتهم في الدرس النحوي العربي، فقد تعايشت العلوم الإسلامية والعربية مع بعضها، وتأثر علماء العربية بما ساد وانتشر في الساحة العلمية والمعرفية في القرون الأولى خاصة زمن تدوين العلوم والتنظير لها، ومن أبرز العلوم العربية المتأثرة بمناهج المتكلمين؛ علم النحو العربي، الذي نشأ لخدمة النص القرآني، فكانت بدايته تحقيقا لغاية لسانية وهي عصمة اللسان من الزلل في تلاوة الكتاب الكريم، ثم تحولت أفكار النحاة في القرن الرابع ليتجهوا بالنحو إلى قِبلة علم الكلام، ويتأثروا بمنهجه وأسلوبه ومصطلحاته، فكانت النزعة الكلامية واضحة في الفكر النحوي العربي، وغدا الدرس النحوي كأنه جزء من علم الكلام في مادته، أو فرع من علم المنطق في قواعده. Abstract This research is a historical study about Arabic grammar, through which it highlighted the influence of the methods, styles and terminology of theologians in the Arabic grammatical lesson. Islamic and Arabic sciences coexisted with each other, moreover Arab scholars were affected by what prevailed and spread in the scientific and knowledgeable field during the first centuries, especially the time of codification of Science and theorizing about it, and one of the most prominent Arab sciences influenced by the curricula of the speakers; Arabic grammar, which was established to serve the Qur’anic text. Its beginning was an investigation of a linguistic goal, which lead to protecting of the tongue in the recitation of the Holy Book, They quote its method, style and terminology, so the verbal tendency was clear in the formulation of Arabic grammatical thought, and the grammatical lesson became as if it were part of the science of theology or a branch of logic, Setting and rooting, methodological and terminological.
مقال
Keywords: النحو؛ علم الكلام؛ النزعة الكلامية؛ الفكر النحوي.